The admissibility of outer continental shelf delimitation claims before the ICJ absent a recommendation by the CLCS (2018)
In the 2017 Maritime Delimitation in the Indian Ocean Case, the International Court of Justice stated that “in appropriate circumstances” maritime delimitation claims beyond 200 nm may be admitted before the Commission on the Limits of the Continental Shelf issues a recommendation. This is a deviation from the Court’s previous approach in the 2016 Nicaragua v. Colombia (Preliminary Objections) Case. This article follows the evolution of the international case law with respect to the admissibility of outer continental shelf delimitation claims absent a final and binding outer limit, and highlights the positive implications of the International Court’s most recent formula. © 2018 Taylor and Francis Group, LLC.